2015
DOI: 10.1177/1933719114549843
|View full text |Cite
|
Sign up to set email alerts
|

Unremitting Cell Proliferation in the Secretory Phase of Eutopic Endometriosis: Involvement of pAkt and pGSK3β

Abstract: Unceasing cell proliferation in the secretory phase of eutopic endometriosis is linked to deregulation of c-kit/SCF-associated signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Endometrial cell proliferation decreased between the proliferative to mid-secretory phases; however, uncontrolled endometrial epithelial cell proliferation can lead to implantation failure and has been observed in the eutopic secretory endometrium of patients with endometriosis (69). Therefore, endometrial cell proliferation is closely related to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cell proliferation decreased between the proliferative to mid-secretory phases; however, uncontrolled endometrial epithelial cell proliferation can lead to implantation failure and has been observed in the eutopic secretory endometrium of patients with endometriosis (69). Therefore, endometrial cell proliferation is closely related to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Especially, p-AKT (Ser473) was highly expressed in endometriotic stromal cells, which led to the reduced decidualization and cell survival. 41,43 Therefore, we evaluated the levels of PN, ILK1, and p-Akt with the hypothesis that PN overexpression may upregulate the expressions of ILK1 and p-Akt. Moreover, we verified that the expressions of ILK1 and p-Akt were inhibited by the PN siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…pathway was activated in endometriosis. Especially, p-AKT was highly expressed in endometriotic stromal cells, leading to the reduced decidualization and cell survival (26,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%